Proteomic Analysis of Human Bladder Epithelial Cells by 2D Blue Native SDS-PAGE Reveals TCDD-Induced Alterations of Calcium and Iron Homeostasis Possibly Mediated by Nitric Oxide - Verma, Nisha; Pink, Mario; Petrat, Frank; Rettenmeier, Albert W.; Schmitz-Spanke, Simone (Journal of Proteome Research, 2015)
A proteomic analysis of the interaction among multiprotein complexes involved in 2,3,7,8-dibenzo-p-dioxin (TCDD)-mediated toxicity in urinary bladder epithelial RT4 cells was performed using two-dimensional blue native SDS-PAGE (2D BN/SDS-PAGE). To enrich the protein complexes, unexposed and TCDD-exposed cells were fractionated. BN/SDS-PAGE of the resulting fractions led to an effective separation of proteins and protein complexes of various origins, including cell membrane, mitochondria, and other intracellular compartments. Major differences between the proteome of control and exposed cells involved the alteration of many calcium-regulated proteins (calmodulin, protein S100-A2, annexin A5, annexin A10, gelsolin isoform b) and iron-regulated proteins (ferritin, heme-binding protein 2, transferrin). On the basis of these findings, the intracellular calcium concentration was determined, revealing a significant increase after 24 h of exposure to TCDD. Moreover, the concentration of the labile iron pool (LIP) was also significantly elevated in TCDD-exposed cells. This increase was strongly inhibited by the calmodulin (CaM) antagonist W-7, which pointed toward a possible interaction between iron and calcium signaling. Because nitric oxide (NO) production was significantly enhanced in TCDD-exposed cells and was also inhibited by W-7, we hypothesize that alterations in calcium and iron homeostasis upon exposure to TCDD may be linked through NO generated by CaM-activated nitric oxide synthase. In our model, we propose that NO produced upon TCDD exposure interacts with the iron centers of iron-regulatory proteins (IRPs) that modulate the alteration of ferritin and transferrin, resulting in an augmented cellular LIP and, hence, increased toxicity.
EVALuna2:9715